Development of a Small-scale Machine for Extraction and Brushing of Sisal Fiber - Barasa, Nelson W (University of Nairobi, 2020)
Sisal fibre is a raw material used in the production ropes, mats, gunny bags, carpets and polymer composites. UNIDO, in 2001, revealed that there is large amount of small-scale sisal in East Africa that is inadequately exploited due to lack of appropriate decortication technology. Small-scale have for a long time relied on tedious and low yielding manual methods that only contributed less than 25% to the total Kenyan sisal fibres exports in 2003. To increase processing of hedge sisal, UNIDO recommended that appropriate small-scale decortication technology should be developed. However, the raspadors developed so far have only focus on extraction ignoring brushing that greatly improves fibre quality. Low grade fibre obtained by these machines is sold at very low prices (Kshs 17 per kg) compared to a better under grade that would be sold at Kshs 175 per kg for brushed fibres. Moreover, research has shown that environmental conditions, fibre surface modification, age and processing methods cause the variability of sisal fibre properties. Howbeit, inadequate research quantifying the variability of sisal fibre properties with processing method was found. Therefore, this project aimed at developing a raspador for extraction and brushing of sisal fibres and quantifying the effects of raspador processing variables on sisal fibre properties. A raspador for extraction and brushing of sisal fibres was designed based on the raspador principle using Autodesk Inventor. It was fabricated and extensively tested at Mechanical Engineering Workshop